Security detention - United Kingdom practice - McGoldrick, Dominic (Case Western Reserve University School of Law, 2009)
This article assesses the role of security detention within the context of a number of the United Kingdom’s anti-terrorism policies. It considers the U.K. provisions on indefinite detention and the judicial response to those policies. Close attention is given to the Prevention of Terrorism Act 2005 (PTA 2005), and in particular the detailed regime of “control orders” it introduced. The different substantive and procedural bases for judicial challenges to control orders are illustrated by reference to the leading judicial decisions. The challenges have principally been based on the human rights provisions in the European convention on human rights. These have been given a degree of domestic incorporation by the Human Rights Act (1998). Consideration is given to the future use of control orders and how an “exit strategy" from them could be devised. Finally, the article analyses the place of security detention within the context of other policy options that form part of an Anti-Terrorism Strategy. It is submitted that none of them is cost-free in human rights terms.